Correlation between Oral Contraceptive Use and the Incidence of Cervical Cancer - Dian Lutfi Rahmawati; Dwi Estuning Rahayu; Koekoeh Hardjito (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Cervical cancer is a malignant tumor that develops in the cervix and is the second most common type of cancer experienced by women in the world. Causes of cervical cancer include HPV infection, use of oral contraceptives, age of marriage, parity and exposure to cigarette smoke. This study aims to determine the correlation between oral contraceptive use and the incidence of cervical cancer. This literature study research involved secondary data derived from the Google Scholar, Research Gate and Science Direct databases. The keywords applied in the study were oral contraceptives, birth control pills AND cervical cancer. The journals involved were searched for similarities, dissimilarities and compared to one another. As mentioned in 11 journals, long-term use of oral contraceptives of ≥5 years could increase the risk of cervical cancer. Furthermore, three journals stated the grade of cervical precancerous lesions of CIN 2/3 as the risk factor of cervical cancer, and two journals stated the grade of cervical cancer of stage 2/2+ as the risk factor of cervical cancer. Based on the chi-square test results, 4 journals presented a significance value (p-value) of <0.05, which indicated a correlation between oral contraceptives and the incidence of cervical cancer. 9 other journals found the highest OR value = 9.11 and the lowest OR = 1.50 which meant that women who used Oral contraceptives were 9 times more at risk of developing cervical cancer. Oral contraceptive use was associated with cervical cancer based on the duration of use of more than 5 years and led to a risk of causing CIN 2/3 among women. There were other factors that could affect the incidence of cervical cancer, namely age of marriage, parity and exposure to cigarette smoke.